Into the Garbage? - Reasons for the Non-use of Technical Innovations in Inpatient Care - Sebastiao, Maria; Hechtel, Nicole; Krueckeberg, Joern (Gesundheitswesen, 2021)
Despite the potentially positive effects of new technologies, innovations are often not well accepted by nurses. The aim of this study was to explore the reasons for not using a distributed alarm system and to derive recommendations for future projects. Three group discussions were held with 14 nurses. Content analysis was used to explore the data. The nursing staff was not involved in the selection and introduction of the technology. A lack of knowledge or interest was not the reason for not using the system. The technology rather interrupted work processes, led to additional workload and exposure to more noise pollution for employees and patients. Technologies must fit into daily work routines. Ideally, nurses should be involved in the development, but at the least, they should be consulted at the time of introduction.
CRIS-Team WoS Importer:2021-09-17